Nuclear service water piping : Oskarshamn Nuclear Power Plant, Figeholm, Sweden. (Case study (Nickel Development Institute (Canada)), 1995)
This booklet provides case studies of nuclear service water piping system in Oskarshamn Nuclear Power Plant.